Project "HorTOCAR": correspondences, agroecology and production of life with the elderly in pandemic times (PerCursos, 2023)
This work proposes a dialogue about old age from the perspective of agroecological practices, in this case, in the context of home gardening as a tools for dialogue and exchange of knowledge for the production of life. The study was conducted in the period of the COVID-19 pandemic and social isolation in 2020 and 2021 with a group of elderly that participated in the HorTOCAR project, a group for exchanging knowledge about home gardening in pandemic times. The method chosen for the research was participant observation through correspondence as proposed by the anthropologist Tim Ingold (2017). It provided the researcher with the necessary methodological support for an active social participation within the group. Even in the context of an on-line group, the proposed activities aimed at various forms of expression through making and experimentation beyond the limits of verbal communication. The group meetings were constituted as a response to the challenges related to the construction of a space for exchanging knowledge and fostering correspondence in the context of social isolation. In addition, the group aimed for the construction of autonomy for the elderly. As a result, it was possible to build a space that would serve the participants, even if isolated, providing them with a place for social encounters capable of producing life despite the uncertainties arising from the historical moment.
Keywords: old age; correspondence; agroecology; multidisciplinary